(untitled) (Journal of Universal Science Research, 2025)
The stylistic device of the epithet plays a crucial role in shaping the expressive and aesthetic qualities of English fiction texts. By attributing distinctive characteristics to objects, people, or events, epithets enrich the narrative, evoke emotions, and enhance imagery. This article explores the function of epithets in literary texts, examining their historical evolution, structural patterns, and semantic impact. Through the analysis of selected examples from English fiction, the study highlights how epithets contribute to the depth of characterization, the creation of mood, and the overall stylistic harmony of a text.